DAMPAK PENGGANDA USAHA KECIL SEKTOR PARIWISATA TERHADAP PERTUMBUHAN PEREKONOMIAN BALI: SUATU PENDEKATAN MODEL INPUT-OUTPUT - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Development in Bali Province Bali based on economic aspect with emphasis at agricultural sector in wide meaning to continue of efforts to settle self sufficiency in food, development of tourism sector with character culture of Bali which is soul by Hinduism, and also small industrial sector and small industry which related to agricultural sector and tourism sector. Objective of the research area: (1) to know contribution of small industry on tourism sector to Bali regional income (gross added value), (2) to know know impact of output and income multiplier generated by small industries at tourism sector toward growth of economics sectors in Bali. This research use approach of Input-Output Tourism Bali year 2000, as source of data and also data-processing method to answer the objective research. Result of research found that: (1) contribution of tourism small enterprise toward Bali regional income (gross added value) is equal to Rp 2.694.049 million or 16,3% from totalizing income of Bali regional. Primary Input Coefficient of torism small small enterprise equal to 0,618 (> 0,5) including is efficient, because it can create wages, salary, profit or enterprise surplus and indirect tax that big, meaning also can become mover machine of Bali economics region, specially indirect and direct society activities who related direct and indirect to the small industry mentioned; (2) The tourism small enterprise has output multiplier impact bigger than average multiplier. This indicates that small industries at tourism sector have ability as trigger of growth of Bali region economics region. Although this small industry have income multiplier impact smaller than average multiplier, but this small enterprise can create income higher toward other economic sectors from each of ones monetary that expended to fulfill request finally. Tourism small enterprise have potential and strategic role to be developed and also personate as trigger of economic growth. Therefore this tourism small enterprise should be developed and constructed , either through capital aid, training of management, and also aid access market, so that powered progressively and professional.
Keywords: Impact, Small Enterprise, Tourism, Input-Output Model